Can Confucianism raise enterprise performance? Evidence from Chinese industrial enterprises in Shandong Province. (29th January 2022) - Zhao, Hongjun; Ding, Zhonghui
The literature in recent years shows that Confucianism has fostered social trust and has contributed to the East Asian economic miracle and China's economic miracle since 1978. However, few studies have analysed the impact of Confucianism on enterprise performance. Based on a national database of Chinese industrial enterprises in Shandong Province, this study finds that enterprises in a more Confucian environment have lower business costs and tend to have a higher debt ratio, increased trust in their business partners, higher labour productivity and employee wages. However, they tend to pay less tax to the state and have a lower productivity level compared to others. We confirmed many so-called conceptual hypotheses related to the impact of Confucianism using enterprise data for the first time, though there are some limitations in this study.